The molecular basis of human 3-methylcrotonyl-CoA carboxylase deficiency - Baumgartner, Matthias R. (American Society for Clinical Investigation, 2001)
Isolated biotin-resistant 3-methylcrotonyl-CoA carboxylase (MCC) deficiency is an autosomal recessive disorder of leucine catabolism that appears to be the most frequent organic aciduria detected in tandem mass spectrometry–based neonatal screening programs. The phenotype is variable, ranging from neonatal onset with severe neurological involvement to asymptomatic adults. MCC is a heteromeric mitochondrial enzyme composed of biotin-containing α subunits and smaller β subunits. Here, we report cloning of MCCA and MCCB cDNAs and the organization of their structural genes. We show that a series of 14 MCC-deficient probands defines two complementation groups, CG1 and 2, resulting from mutations in MCCB and MCCA, respectively. We identify five MCCA and nine MCCB mutant alleles and show that missense mutations in each result in loss of function.